IMPROVING STUDENTS’ READING COMPREHENSION BY USING PROBLEM-BASED LEARNING METHOD AT XI MIPA 5 SMA NEGERI 1 BADEGAN PONOROGO IN ACADEMIC YEAR 2021/2022 - Setyaningrum, Ratih; Indriastuti, Niken Reti; Asiyah, Siti (Universitas Muhammadiyah Ponorogo, 2023)
This research aimed to explain how the Problem-Based Learning Method improved the reading comprehension of XI MIPA 5 students at the SMAN 1 Badegan and to indentify what aspects of reading learning can be improved. The researcher used classroom action research. This research had 2 cycles consisting of planning, implementation, observation, and reflection. In this research, the researcher used 3 instruments: observations, questionnaires, and tests to measure student achievement and to know student responses after implementation of Problem-Based Learning in reading comprehension. The result of the study showed that students reading comprehension was improved. This was proven by the result of test which improved from 7% in cycle 1 to 100% in cycle 2. Then, the the result of the questionnaires which improved from 78% in cycle 1 to 98% in cycle 2. Furthermore, this study was also proven by the result of observation which improved from 65% in cycle 1 to 95% in cycle 2. Based on finding data from 3 instruments, the researcher concluded that the implementation of the Problem-Based Learning method was successful to improve students’ reading comprehension at X MIPA 5 SMA Negeri 1 Badegan in academic year 2021/2022.